2014
DOI: 10.1155/2014/231895
|View full text |Cite
|
Sign up to set email alerts
|

Brooke-Spiegler Syndrome: A Rare Entity

Abstract: Brooke-Spiegler syndrome is a rare entity. It is an autosomal dominant syndrome in which multiple trichoepitheliomas, cylindromas, or other adnexal tumors are seen. Very few cases of Brooke-Spiegler syndrome are reported in the literature. We came across a 40 -year-old female in which multiple trichoepitheliomas and cylindromas were seen on scalp. In view of clinical history and histopathological examination it was diagnosed as Brooke-Spiegler syndrome. We report this case because of its rarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…To date, different therapeutic approaches have been implemented. However, surgical excision remains the gold standard with the lowest rate of relapse compared to dermabrasion, electrodessication, cryotherapy, radiotherapy, argon, and CO 2 lasers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, different therapeutic approaches have been implemented. However, surgical excision remains the gold standard with the lowest rate of relapse compared to dermabrasion, electrodessication, cryotherapy, radiotherapy, argon, and CO 2 lasers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,3,8 These mutations are found roughly in 80-85% of BSS cases. 7 However, in the remaining cases one should take into account that de novo mutations of other germline genes, alterations in noncoding regions, large chromosomal rearrangements or deletions, or other changes not detected by conventional sequencing can be present.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually poorly differentiated, and show overlapping cytomorphological and immunohistochemical features of apocrine and eccrine lineage. 8,9 Nevertheless, Sellheyer recently proposed that spiradenomas and cylindromas are not sudoriparous but poorly differentiated follicular tumors derived from the hair follicle bulge. He based his proposal on the increased expression of CD200 in both types of lesions whereas, in his extensive study, he had shown that tumors classified as eccrine in lineage (hidradenoma, poroma, dermal duct tumor, and hidroacanthoma simplex) were CD200 negative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations